(untitled) (Research, Society and Development, 2022)
In home care processes, where multidisciplinary health teams take care of their patients at home, there are several challenges for resource management and remote monitoring, where, sometimes, resources are not used in main priority situations. The advent of technology, the availability of data in management systems and the new decision-making support tools bring enormous possibilities, financial return and greater comfort for patients and families. This work aims to present the application of machine learning, using the CRISP-DM methodology, to identify patients with a greater chance of hospitalization or to pass away at home.